Bovine tuberculosis in working foxhounds: lessons learned from a complex public health investigation. (9th October 2019) - Phipps, Emily; McPhedran, Kate; Edwards, David; Russell, Katherine; O'Connor, Catherine M.; Gunn-Moore, Danielle A.; O'Halloran, Conor; Roberts, Tony; Morris, Jill
Abstract: In 2017, Public Health England South East Health Protection Team (HPT) were involved in the management of an outbreak of Mycobacterium bovis (the causative agent of bovine tuberculosis) in a pack of working foxhounds. This paper summarises the actions taken by the team in managing the public health aspects of the outbreak, and lessons learned to improve the management of future potential outbreaks. A literature search was conducted to identify relevant publications on M. bovis . Clinical notes from the Public Health England (PHE) health protection database were reviewed and key points extracted. Animal and public health stakeholders involved in the management of the situation provided further evidence through unstructured interviews and personal communications. The PHE South East team initially provided 'inform and advise' letters to human contacts whilst awaiting laboratory confirmation to identify the infectious agent. Once M. bovis had been confirmed in the hounds, an in-depth risk assessment was conducted, and contacts were stratified in to risk pools. Eleven out of 20 exposed persons with the greatest risk of exposure were recommended to attend TB screening and one tested positive, but had no evidence of active TB infection. The number of human contacts working with foxhound packs can be large and varied. HPTs should undertake a comprehensive risk assessment of all potential routes of exposure, involve all other relevant stakeholders from an early stage and undertake regular risk assessments. Current guidance should be revised to account for the unique risks to human health posed by exposure to infected working dogs.